1987
DOI: 10.1108/eb002640
|View full text |Cite
|
Sign up to set email alerts
|

Devaluation, Inflationary Expectations and Stabilisation in Peru

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Gylfason and Risager (1984), Branson (1986), Solimano (1986), Roca and Priale (1987), Horton and McLaren (1989), and Gylfason and Radetzki (1991) provide evidence from macroeconomic models of the effect of exchange rate devaluation on the trade balance. Apart from Gylfason and Risager (1984) and Gylfason and Radetzki (1991), the results of these studies show that devaluation worsens the trade balance or balance of payments.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Gylfason and Risager (1984), Branson (1986), Solimano (1986), Roca and Priale (1987), Horton and McLaren (1989), and Gylfason and Radetzki (1991) provide evidence from macroeconomic models of the effect of exchange rate devaluation on the trade balance. Apart from Gylfason and Risager (1984) and Gylfason and Radetzki (1991), the results of these studies show that devaluation worsens the trade balance or balance of payments.…”
Section: Literature Reviewmentioning
confidence: 96%
“…The macro-simulation approach (Gylfason and Schmid, 1983;Gylfason and Risager, 1984;Solimano, 1986;and Roca and Priale, 1987). This approach uses simulation models to analyze the impact of exchange rate changes on output.…”
Section: Introductionmentioning
confidence: 99%
“…Solimano (1986) constructed a macroeconomic model for Chile and concluded that devaluation was contractionary in the short to medium run. Roca and Priale (1987) constructed a macroeconomic model for the Peruvian economy and concluded that devaluations were contractionary.…”
Section: Introductionmentioning
confidence: 99%
“…(1976) observed that currency devaluation can affect tax collection on both sides (increase or decrease).The behavior depends upon the impact of tax on supply chain and value chain and velocity of circulation of money. Aghevli and Khan (1978), Gulhati et al (1986) studied this phenomenon in India , Roca and Priale (1987) in their study on Peru, Hossain (1987) in his study on Bangladesh found similar results. Liam P. Ebrill and Janet Gale Stotsky (1999) found that deprecation of local currency leads to decrease in taxes on trade.…”
Section: Introductionmentioning
confidence: 80%